PSYCHOLOGICAL EDUCATION IN THE CONDITIONS OF REMOTE QUALIFICATION - Олексенко, Светлана; Хоменко, Елена (SWorldJournal, 2021)
The article considers the problem of psychological education in the process of advanced training in distance format, in particular, the feasibility of introducing training modules of psychological orientation while improving professional competence in dis